Resonance and nonlinearity: A survey - Mawhin, J. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
This paper surveys recent results about nonresonant and resonant periodically forced nonlinear oscillators. This includes the existence of periodic, unbounded or bounded solutions for bounded nonlinear perturbations of linear and piecewise-linear oscillators, as well as of some classes of planar Hamiltonian systems.